Пак Кин Хе – президент республіки Корея, залізна леді Азії - Матлай, Любава (Lviv Politechnic Publіshing House, 2016)
Висвітлено нелегкий життєвий шлях та неординарне політичне бачення однієї із найвизначніших азійських політиків, першої за останні тисячу років жінки-президента Республіки Корея Пак Кин Хе. Її обрання на вищий пост у державі було вражаючим досягненням, враховуючи, що Південна Корея має найвищий рівень гендерної нерівності серед розвинених країн світу. The paper deals with the main aspects of the political biography and reviews the first female president in Korea’s history in the 21st century Ms. Park Geun-Hye, whoalso is the first woman head of the state in the modern history of Northeast Asia. Her election to the highest post in the state was an especially impressive achievement considering that SouthKorea has the highest level of gender inequality among developed countries in the world. In this country and in the whole Northeastern Asian region politics has been a male-dominated occupation and women have been underrepresented. Special attention is paid to factors which conditioned success of the presidential elections winner. Inauguration of the president of the ROK ParkGeun-Hye was a turning point in the role of women in South Korean politics. Finally, the president Park is a rare female leader in a male-dominated political system. The author of the paper examines the role of familial ties in Park Geun-Hye’s political history. It is found that the basic foreign policy strategy of President Park’s administration is politics of trust which consists of three pillars: trust diplomacy and multilateral cooperation in Asia; strong defense and strong deterrence; the Korean peninsula trust process. The leaders of Asia’s countries shared common understanding of the need to upgrade bilateral and multilateral strategic partnership to higher level of cooperation for peace and prosperity of the international community. Тhe author considers the approach of President Park towards the USA, Japan, China, North Korea. The President of South Korea is a proponent of negotiating between the two Koreas, rather than adopting military solutions. In her reconciliation project, the peace building process for two Koreas should start with demilitarization, followed by economic and political integration.
Ms. Park Geun-Hye: the president of the Republic of Korea, “Iron lady” of Asia
Keywords: Республіка Корея; перша жінка-президент; лідер нації; зовнішньополітичний курс; регіональна політика; The Republic of Korea; the first female president; the leader of the nation; foreign policy; regional policy